MODEL KREATIF PEMBELAJARAN P4 PADA PENDIDIKAN KECAKAPAN HIDUP PRODUKSI JAMUR MERANG - Yudi, Yudi (JIV-Jurnal Ilmiah Visi, 2010)
The instruction ofP4 was found not satisfactory to meet the instruction objectives employing the traditional ,nuuel. lt71S research developed a creative model for P4 instruction particularly for life skills using descriptive methods. Instruments to collect data included check list, evaluation sheets for tryout and implementation. After try out process and revision, this research could developed P4 Instruction Model for Life Skill to Produce Mushroom. This mode/ has been able to solve the instructional problems in UPTD SKB in Bekasi District.